Protest, subjekt og udsagn i to nutidige egyptiske eksperimentalfilm - Ørskov, Maj; Lund, Jacob (K&K - Kultur og Klasse, 2023)
The films The Square (2013) by Jehane Noujaim and In the Last Days of the City (2016) by Tamer El Said both relate to the 2011 uprising in Cairo and its aftermath, albeit in very different ways. The article analyses how the films in each their way mobilise and articulate – rather than represent – political protest and a subject of this protest. The analysis is guided by the hypothesis that parts of critical Egyptian contemporary art, experimental film in particular, have increasingly moved away from the immediate endeavours of the uprising to establish a collective subject and toward a reparation of more unstable, politically seeking subjectivities with a view to destabilise the current authoritarian regime in Egypt. With reference to the political changes in Egypt in the period from 2011 to 2016 the article explores the enunciational conditions for protest in the span between a collectively manifest subject and fragmented, searching subjectivities. In dialog with Elizabeth Kassab’s notion of political humanism, Jacques Rancière’s understanding of political subjectivity, and Giorgio Agamben’s notion of destitution the authors analyse the visual articulation of protest – also where it is not readable as statement and iconography but, on the contrary, precisely insisting in its absence – and try to connect these analyses to reflections on the changing temporality and spatiality of uprising.